Studi Penelitian Tindakan Kelas: Upaya Peningkatan Kosa Kata Bahasa Arab Siswa - Navis Irham (Yayasan Salam Cerdas Al-Fattah, 2025)
This study aims to improve the mastery of Arabic vocabulary of 8th grade students of MTs Nurul Islam Indonesia Medan through the application of Tahsin method. The method used is Classroom Action Research (PTK) Kurt Lewin model which consists of four stages: planning, action, observation, and reflection. The research was conducted in two cycles. The instruments used included initial test, post-test, observation sheet, and documentation. The results showed an increase in students' vocabulary skills from cycle I to cycle II. In cycle I, the average score obtained by students was 35 with a percentage of completeness of 78%, while in cycle II it increased to an average score of 40 with a percentage of completeness of 89%, which is in the “Good” category. This improvement was achieved through various efforts such as the preparation of visual media-based lesson plans, the use of relevant thematic images, vocabulary pronunciation exercises through the Tahsin method, and strengthening student involvement in active learning. The findings prove that the Tahsin method is effective in improving students' Arabic vocabulary and can be an applicable learning strategy in the madrasah context.